ANALISIS PENERIMAAN PAJAK GALIAN GOLONGAN C TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA AMBON - Lasamahu, Helena Griffith; Mofu, Aprillia Cenyo (SKETSA : Jurnal Ilmu-Ilmu Sosial, 2021)
The Main of focus, this research is to know how big faction the influence of dig tax C and to earn the original of Ambon town area, faction dig tax C of pennant sector, during five years the fee always having or institution doing the activity of exploitation and various exploiting of faction dig C material tax,so it influential for acceptance receiving of faction dig tax C. during five years, faction dig material type C has big advantages (Use value) and can yield economic value (Economic Value). if both of the positive area acceptance than. It will be doing a good positive to country acceptance. To get the purpose of this research applied faction dig tax C data the year 2005-2009 and the eam data of original area the year 2005-2009 analitycal method which is using is simple regression that is the analysis to know. The relation ship or correlation between the development of acceptance of faction dig tax C through the earn of the original Ambon town area.